Answer:
Options (1), (2), (3) and (7)
Step-by-step explanation:
Given expression is
.
Now we will solve this expression with the help of law of exponents.
![\frac{\sqrt[3]{8^{\frac{1}{3}}\times 3} }{3\times2^{\frac{1}{9}}}=\frac{\sqrt[3]{(2^3)^{\frac{1}{3}}\times 3} }{3\times2^{\frac{1}{9}}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%5B3%5D%7B8%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Ctimes%203%7D%20%7D%7B3%5Ctimes2%5E%7B%5Cfrac%7B1%7D%7B9%7D%7D%7D%3D%5Cfrac%7B%5Csqrt%5B3%5D%7B%282%5E3%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Ctimes%203%7D%20%7D%7B3%5Ctimes2%5E%7B%5Cfrac%7B1%7D%7B9%7D%7D%7D)
![=\frac{\sqrt[3]{2\times 3} }{3\times2^{\frac{1}{9}}}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%5Csqrt%5B3%5D%7B2%5Ctimes%203%7D%20%7D%7B3%5Ctimes2%5E%7B%5Cfrac%7B1%7D%7B9%7D%7D%7D)
![=\frac{2^{\frac{1}{3}}\times 3^{\frac{1}{3}}}{3\times 2^{\frac{1}{9}}}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B2%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Ctimes%203%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%7D%7B3%5Ctimes%202%5E%7B%5Cfrac%7B1%7D%7B9%7D%7D%7D)
![=2^{\frac{1}{3}}\times 3^{\frac{1}{3}}\times 2^{-\frac{1}{9}}\times 3^{-1}](https://tex.z-dn.net/?f=%3D2%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Ctimes%203%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%5Ctimes%202%5E%7B-%5Cfrac%7B1%7D%7B9%7D%7D%5Ctimes%203%5E%7B-1%7D)
![=2^{\frac{1}{3}-\frac{1}{9}}\times 3^{\frac{1}{3}-1}](https://tex.z-dn.net/?f=%3D2%5E%7B%5Cfrac%7B1%7D%7B3%7D-%5Cfrac%7B1%7D%7B9%7D%7D%5Ctimes%203%5E%7B%5Cfrac%7B1%7D%7B3%7D-1%7D)
![=2^{\frac{3-1}{9}}\times 3^{\frac{1-3}{3}}](https://tex.z-dn.net/?f=%3D2%5E%7B%5Cfrac%7B3-1%7D%7B9%7D%7D%5Ctimes%203%5E%7B%5Cfrac%7B1-3%7D%7B3%7D%7D)
[Option 2]
[Option 1]
![2^{\frac{2}{9}}\times 3^{-\frac{2}{3} }=(\sqrt[9]{2})^2\times (\sqrt[3]{\frac{1}{3} } )^2](https://tex.z-dn.net/?f=2%5E%7B%5Cfrac%7B2%7D%7B9%7D%7D%5Ctimes%203%5E%7B-%5Cfrac%7B2%7D%7B3%7D%20%7D%3D%28%5Csqrt%5B9%5D%7B2%7D%29%5E2%5Ctimes%20%28%5Csqrt%5B3%5D%7B%5Cfrac%7B1%7D%7B3%7D%20%7D%20%29%5E2)
![=(2^2)^{\frac{1}{9}}\times (3^2)^{-\frac{1}{3} }](https://tex.z-dn.net/?f=%3D%282%5E2%29%5E%7B%5Cfrac%7B1%7D%7B9%7D%7D%5Ctimes%20%283%5E2%29%5E%7B-%5Cfrac%7B1%7D%7B3%7D%20%7D)
[Option 3]
![2^{\frac{2}{9}}\times 3^{-\frac{2}{3} }=(2^2)^{\frac{1}{9}}\times (3^{-2})^{\frac{1}{3} }](https://tex.z-dn.net/?f=2%5E%7B%5Cfrac%7B2%7D%7B9%7D%7D%5Ctimes%203%5E%7B-%5Cfrac%7B2%7D%7B3%7D%20%7D%3D%282%5E2%29%5E%7B%5Cfrac%7B1%7D%7B9%7D%7D%5Ctimes%20%283%5E%7B-2%7D%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%20%7D)
[Option 7]
Therefore, Options (1), (2), (3) and (7) are the correct options.
Answer: Nancy needs 26 minutes to driving to work.
Explanation:
Since we have given that
Time taken in eating breakfast = 10 minutes
Time taken in making her bed = 5 minutes
Let the total time taken by her in doing routine activities be x
Time taken in getting dressed is given by
![\frac{1}{3}x](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7Dx)
So, According to question,
![\frac{x}{3}+10+5=35\frac{1}{2}\\\\\frac{x}{3}+15=\frac{71}{2}\\\\\frac{x}{3}=\frac{71}{2}-15\\\\\frac{x}{3}=\frac{71-30}{2}=\frac{41}{2}\\\\x=\frac{123}{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B3%7D%2B10%2B5%3D35%5Cfrac%7B1%7D%7B2%7D%5C%5C%5C%5C%5Cfrac%7Bx%7D%7B3%7D%2B15%3D%5Cfrac%7B71%7D%7B2%7D%5C%5C%5C%5C%5Cfrac%7Bx%7D%7B3%7D%3D%5Cfrac%7B71%7D%7B2%7D-15%5C%5C%5C%5C%5Cfrac%7Bx%7D%7B3%7D%3D%5Cfrac%7B71-30%7D%7B2%7D%3D%5Cfrac%7B41%7D%7B2%7D%5C%5C%5C%5Cx%3D%5Cfrac%7B123%7D%7B2%7D)
Now, we need to find the time taken in driving to work which is given by
![\frac{123}{{2}-\frac{71}{2}=\frac{52}{2}=26\ minutes](https://tex.z-dn.net/?f=%5Cfrac%7B123%7D%7B%7B2%7D-%5Cfrac%7B71%7D%7B2%7D%3D%5Cfrac%7B52%7D%7B2%7D%3D26%5C%20minutes)
Hence, Nancy needs 26 minutes to driving to work.
Answer:
7
Step-by-step explanation:
1. Lets Combine Like Terms. The only combineable terms are 8 and 8. So if we combine them they will equal 16. And we will have (2n+2)=16
2. Let's isolate the variable. We can do this by subtracting 2 from both sides. This will come out to 2n+14.
3. Let's further isolate the variable. We can do this by dividing both sides by two, which will finally come out to n=7
Answer:
B
Step-by-step explanation:
V = 4/3 * radius^3 * pi = 4/3 * 4^3 * pi = 256 /3 * pi
Answer:
Step-by-step explanation:
The answer is A. 16+10+20= 46